PENTINGNYA ACFTA ( ASEAN-CHINA FREE TRADE AREA) BAGI INDONESIA - , FITRIAH NAMSA; , Drs. Muhadi Sugiono, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The cooperation between nations becomes an absolute thing for nations in the world. This cooperation needs to be conducted because every nation believes that this international cooperation can give profit or benefit for all since there is an agreed norm and share belief. One of the forms of the cooperation between areas is ACFTA, Since the free trade cooperation between ASEAN and China has been legalized in January 2010, ASEAN and China tried to develop a strategic relation between them so that they could get a maximum benefit for each commerce so that they could improve their economy position in a better way. According to the view of Neoliberal Institusionalism, it is stated that the international institution helps to improve the cooperation between nations in the world and, thus, this helps to decrease the incredulity between nations as well as to alleviate the fear from one nation to the others which are assumed to be a traditional problem that related to the anarchy of the internasional. Indonesia, as one of the nations that involves on the assembling of this ACFTA, also has the same purpose. The growth of economy in China which is very advance and is supported by the high export growth in many countries becomes the challenge for many ASEAN members to get the benefit from this. This study explains about how and what the interests of Indonesia in this ACFTA cooperation are, especially the economy and political interests of Indonesia. It is because of the growth of the economy of China which is very advance and known as a new raising star country.